2010
DOI: 10.1111/j.1365-2648.2010.05345.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding major depressive disorder among middle‐aged African American men

Abstract: It is important to approach depression diagnoses from a broad perspective rather than as a limited list of symptoms. Healthcare providers would benefit from taking into account cultural factors, gender and age, examining them carefully in relation to the development of depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…In another interview study with 10 African American men who self-reported that they had experienced depression, Bryant-Bedell and Waite (2010) uncovered that participants had experienced depression in the past but did not realize that they were depressed. Participants in their study described feelings of depression, including irritability, isolation, and depressed mood; however, they did not seek treatment (Bryant-Bedell & Waite, 2010). Rather, men in this study reported that they only sought treatment after a "breakdown."…”
Section: Research-article2016mentioning
confidence: 84%
See 1 more Smart Citation
“…In another interview study with 10 African American men who self-reported that they had experienced depression, Bryant-Bedell and Waite (2010) uncovered that participants had experienced depression in the past but did not realize that they were depressed. Participants in their study described feelings of depression, including irritability, isolation, and depressed mood; however, they did not seek treatment (Bryant-Bedell & Waite, 2010). Rather, men in this study reported that they only sought treatment after a "breakdown."…”
Section: Research-article2016mentioning
confidence: 84%
“…These breakdowns ranged from the simple realization that they were not feeling like themselves to encouragement to seek help from members of their social support networks to suicide ideation and "hitting rock bottom." Bryant-Bedell and Waite (2010) concluded that better mental health screening efforts are needed and that providers must account for gender and cultural differences to better recognize depression in African American men.…”
Section: Research-article2016mentioning
confidence: 99%
“…In order to behave in line with masculine ideals, particularly in studies including participants with a depression diagnosis, men perceived a need to close up when faced with emotional distress [22,26,27,30,46,48] . This phenomenon appears to already exist at the discursive level, when men were found to use fewer words and metaphors, compared to women, to describe their emotions during interviews [30] .…”
Section: Closing Upmentioning
confidence: 99%
“…In US-based studies, African-American men reported on the consequences of sociostructural factors such as unemployment, homelessness, racism, and sexism on their mental health [23,46] .…”
Section: Semistructured Interviewsmentioning
confidence: 99%
“…These findings reflect literature documenting African-American culture, family and religion as crucial resources to alleviate distress and assist coping. [41][42][43]51 Our work resonates with Becker and Newsom's identification of resiliency as a key value in African-Americans' struggle for social justice and freedom: "African heritage, cataclysmic disruptions caused by slavery, ensuing historical eras such as Reconstruction and Jim Crow, and continuing racial oppression have all reinforced an emphasis on overcoming obstacles against all odds. The resulting values have been characterized as a 'survival arsenal."…”
Section: Discussionmentioning
confidence: 86%